Spontaneous and transient hyperglycemia before sleep in a patient with glaucomatous blindness and diabetes: A case reprt. Issue 8 (February 2019) - Sun, Zhan-Zhan; Xia, Fang; Du, Si-na; Li, Wei
Abstract: Rationale: The peak of blood glucose was during 9 PM to 3 AM. There is a stable, spontaneous and short-term abnormal increase of blood glucose. The pathophysiological mechanism is unknown. It is speculated that the cause might be the imbalance of the glucose-regulating hormone that is caused by the disorder of the biological clock system. Patient concerns: The case was a 73-year old man with bilateral glaucoma (only mild light perception) and was hospitalized to establish a viable hypoglycemic plan. He received 4 shots of insulin enhancement, oral meditation, pre-mixed insulin treatment during the 22 days. However, his blood glucose had been spontaneously increased from 9 PM to 3 AM which was the highest of the day, and then resumed by itself. Insulin intervention was effective. Diagnosis: Glaucomatous blindness and diabetes, spontaneous and transient hyperglycemia before sleep. Interventions: We used insulin aspart 3u when we found hyperglycemia three times at 9 PM and it was effective. Without intervention, blood sugar will automatically improve in the morning. Outcomes: During the late night and early morning, there is a stable, spontaneous and short-term transit abnormal increase in blood glucose, which suggests the complexity of blood glucose adjustment. Lessons: Due to the case specialty, we could not do the systematic review of the study. However, it improves the awareness of the abnormal periodically increase of blood glucose during the special periods, and provides with a reference for clinical research of dawn and dusk phenomenon. Multi-point blood glucose monitoring or dynamic blood glucose monitoring throughout the day is of great significance for the detection of special types of hyperglycemia.